2013
DOI: 10.2486/indhealth.ms1354
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Factors Associated with Suicidal Ideation and Depressive Symptoms among Middle-aged Workers in Japan

Abstract: The purpose of this study was to assess middle-aged Japanese workers for possible gender differences in the risk factors associated with depressive symptoms and suicidal ideation. 5,878 workers (40-60 yr of age) (3,631 males and 2,247 females) were recruited from randomly selected companies in northern Japan. Demographic and lifestyle factors, suicidal ideation rate, and the data for the Brief Job Stress Questionnaire (BJSQ) and the Center for Epidemiologic Studies for Depression scale (CES-D) were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
2
22
2
3
Order By: Relevance
“…Many other studies also support that unemployment, low job compatibility, unmarried state, absence of stress reduction technique, female gender, low education level, childhood trauma, previous mental disorder, poor self-perceived health state, financial strain and poor social support are risk factors of suicide in general population. 12,[16][17][18] But Almeida et al 18 insisted that male gender and higher education level were independently associated with suicidal ideation, which is opposite to our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Many other studies also support that unemployment, low job compatibility, unmarried state, absence of stress reduction technique, female gender, low education level, childhood trauma, previous mental disorder, poor self-perceived health state, financial strain and poor social support are risk factors of suicide in general population. 12,[16][17][18] But Almeida et al 18 insisted that male gender and higher education level were independently associated with suicidal ideation, which is opposite to our study.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be explained, at least in part, by our study population. It has been reported that an advanced cancer stage was significantly associated with suicidal ideation in males, but not in females . In a study examining the use of suicide prevention centers among general population found that females were more likely to seek help and were benefited more from contact with these facilities .…”
Section: Discussionmentioning
confidence: 97%
“…This may be explained, at least in part, by our study population. It has been reported that an advanced cancer stage was significantly associated with suicidal ideation in males, but not in females [40]. In a study examining the use of The above three adjusted variables with p-value are 'cared by others', 'have no chemotherapy history' and 'have no depression symptoms' respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In Japan, several studies concluded that regular workers also had worse health status due to additional responsibilities and longer work hours12, 13 ) . Owing to various work preferences, both regularly employed and non-regularly employed women had different factors that threatened their health.…”
Section: Findings From Previous Studies: Associations Between Non-regmentioning
confidence: 99%